The Role of Islamic Education Teachers Competency in Improving the Quality of Education - Zuhaeriah Zuhaeriah; Moh. Ali; Yusra Yusra (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2020)
This study discusses the urgency of the competency of teachers on the subjects of Islamic religious education. This study used descriptive qualitative method and gather data through observation, interview, and documentation. Data analysis was carried out through reduction, data presentation, and data verification that ended with checking the validity of the data. The results of this study shows that competence of teachers in junior high school is adequate. The role of teachers in improving the quality of teaching, positions which directly determine the success, considering the teacher as a figure who is directly involved in learning in the classroom. All of these roles requires more concrete effort, and directly touch to the needs of students in order to get better the quality of learning. The efforts made by the Islamic religious education teachers in improving the quality of education including the provision of guidance to students, advice, supervision of students, providing motivation and rewards, using varied teaching methods, and personal approach to students. Supporting factors include the existence of good cooperation from principals, teachers, parents, staff, students and the local community, the infrastructure, the competent teachers, and safe and orderly environment. Inhibiting factors include the lack of instructional media; in this case the writer mean is computer and LCD, the lack of participation and support fromstudents’ parent. As for efforts to deal with is as follows: add computer and LCD and establish good coordination with parents.